eyond regional heterogeneities. The familiar and the academic in teacher researchers at argentine universities (2022-2023) (Papeles, 2024)
In recent years there have been many contributions from gender and science studies at the national and international level. They have exhaustively analyzed the unequal insertion of women and men in the scientific field and some of them have pointed out the implications of privacy in academic careers. However, there have been few who have addressed the issue in terms of articulation of spheres. This article proposes to be a contribution to this field of inquiry by proposing as its objective to explore from a gender perspective the articulations between academic and reproductive work in the trajectories of people who carry out teaching and research in Argentina. The work is part of a longer-range project interested in mapping structural heterogeneity and differential capacities for the production and circulation of knowledge. In this framework, a qualitative study of trajectories was carried out through interviews with research teachers from different regions of the country. As results of the study, it is highlighted that gender inequalities in the academic field cannot be thought about without attending to the ways in which it is articulated with reproductive work and this transcends regional and institutional differences.
Keywords: Gender inequalities; academic career; paid and reproductive work articulation; universities